Беларуская Народная Рэспубліка - Украінская Народная Рэспубліка: Некаторыя асаблівасці шляху і ўзаемаадносін. (Zaporizhzhia Historical Review, 2021)
This problem hardly has been investigated in Soviet historiography. Rare mentions of it in historical literature and other humanities were made in an utterly negative sense, though the representatives of BPR and UPR struggled for what we possess now – independent sovereign states in Byelorussia and Ukraine. The prominent splash of publications devoted to the subject (mostly in Ukrainian historiography, but in Byelorussian as well) has become possible only within the connections with geopolitical processes in the end of 80th – beginning of 90th .